Features of the hemodynamic state in female athletes with disabilities - Zakharova A.V.; Mekhdieva K.R.; Umut Batin Pinar (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the features of the hemodynamic state and aerobic performance of athletes with disabilities to optimize the training process. Methods and structure of the study. Hemodynamic parameters and the results of stress testing were studied in athletes with disabilities involved in cyclic sports (skiing, athletics, swimming and orienteering (n=59). All data obtained were further compared with similar indicators of healthy female racers (n =89). Results and conclusions. It was revealed that, despite the fact that a decrease in resting heart rate determines the physiological adaptation of the cardiosystem to regular training in endurance sports, no significant differences in heart rate in the orthotest were found in the groups of examined female athletes. When analyzing the functional state of athletes, it is advisable to take into account the parameters of the hemodynamic state, especially in the vertical position of the body. For the full development of the sports potential of athletes with disabilities, stage-by-stage comprehensive control in the training process and its individualization are necessary.